PROFESSIONAL AND COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS OF ENGLISH AND ITS SIGNIFICANCE - O.I. Yadgarova, (EPRA International Journal of Research and Development (IJRD), 2023)
This article describes the professional and communicative competence of future English teachers and its content. The development of professional and communicative competence of a future English teacher as a mature specialist should help young people find their place in work, get a quality education, acquire high-quality language skills, develop information competencies, form interpersonal social and cultural communication. In this article, we have interpreted the opinions of many researchers regarding professional and communicative competence. In conclusion, the qualities of the professional and communicative competence of the future English teacher are highlighted. Also, when collecting all the considered components, the content and essence of professional and communicative competence and the formation of the most complex qualities of a person's personality, which are interconnected and mutually demanding, are clearly manifested.